Noise Levels During Laparoscopic Procedures In Operation Theatres: An Observational Study In A Tertiary Care Hospital In Southern India (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Noise pollution in operating theatres has deleterious effects on patient outcomes and staff performance. At the same time, the use of noisy technological equipment in operation theatres has increased in recent years. In light of this trend, it can be assumed that noise pollution in operating theatres remains challenging for patients and providers.Objective: To measures noise levels during laparoscopic procedures in operation theatres of a tertiary care hospital in Southern India and compare them with the recommended standards.Methods: In this cross-sectional observational study, the noise level in the operating theatre of a tertiary care hospital in Southern India during laparoscopic procedures was evaluated using a Decibel Meter from January 2022 and June 2022. Statistical analysis was done using descriptive statistics and one-way ANOVA.Results: Noise levels between 73.68 dB(A) and 49.30 dB(A) during laparoscopic procedures exceeds national and international recommended standards. The highest noise level is observed in the extubation phase of laparoscopic surgery, followed by the surgery and induction phases.Conclusion: Prolonged exposure to high levels of noise during laparoscopic procedures in operating theatres is a hazard to surgeons, anesthetists, personnel, and patients. Government, healthcare professionals, and other agencies should discuss guidelines for improving measures to reduce noise in operation theatres.